2021
DOI: 10.25259/ijmio_8_2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic changes in gastric carcinoma

Abstract: Gastric cancer remains highly prevalent and accounts for a notable proportion of global cancer mortality and this is associated with poor survival rates. Understanding the molecular genetic changes of gastric carcinoma may offer an insight into its pathogenesis helps in identifying new biomarkers, aid prognostication, and novel treatment targets. Over a past few decades, advances in technology and high throughput analysis have improved understanding of the molecular genetic aspects of gastric cancer. In this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 149 publications
0
6
2
Order By: Relevance
“…26 In comparison to the above findings, some studies have shown high intact pRb (up to 87%) or increased Rb expression in gastric cancer and say that this increased expression in early gastric cancer could have diagnostic values. 13,14,16,27 In the current study, only 29.5% of cells had altered Rb gene expression, indicating that Rb mutations are less frequent in gastric cancer than in the Constancia et al study. 25 Further investigations are required to determine the Rb gene correlation to the grade and stage of tumors.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…26 In comparison to the above findings, some studies have shown high intact pRb (up to 87%) or increased Rb expression in gastric cancer and say that this increased expression in early gastric cancer could have diagnostic values. 13,14,16,27 In the current study, only 29.5% of cells had altered Rb gene expression, indicating that Rb mutations are less frequent in gastric cancer than in the Constancia et al study. 25 Further investigations are required to determine the Rb gene correlation to the grade and stage of tumors.…”
Section: Discussioncontrasting
confidence: 51%
“…2,9,12,14,15 Compared to normal or pre-malignant tissues, some studies have documented decreased Rb gene product (pRb) in gastric cancer; therefore, it has diagnostic value in the early stages of the disease. 11,13,16 At the same time, studies in pre-malignant states report increased Rb expression. 14 There are also reports of gastric cancer that suggest Rb gene deletion.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chronic or acute infection by pathogens is a severe threat to humans. H. pylori is one of the pathogens involved in gastric disorders [1][2][3][4][5][6]. Infection by H. pylori not only induces gastric damage but in severe cases promotes gastric cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is one of the leading causes of mortality worldwide. H. pylori, a common gastric pathogen, is considered to be one of the most important carcinogens involved in gastric cancer [1][2][3][4][5][6]. Although only 2% of infected individuals develop cancer, it also causes other gastric complications such as ulcer and gastritis.…”
Section: Introductionmentioning
confidence: 99%